Armenian-Turkish Relations during the Years of independence of the RA - Minasyan, Edik (History and Culture, 2021)
A comprehensive examination of the relevant facts in the article shows that Turkey was one of the first to recognize the independence of Armenia, but no diplomatic relations were established between the countries, since Ankara presented the Armenian authorities some preconditions: not to mention the 1915 Armenian Genocide, to renounce claims officially, to put pressure on to stop the struggle for Nagorno-Karabakh, to recognize the sovereignty and territorial integrity of Azerbaijan. At the same time, Turkey demanded that the Republic of Armenia refrain from actions contrary to the interests of Turkey and in any way neutralize the anti-Turkish activities of the Armenians of the Diaspora. The Republic of Armenia rejected these preconditions and requirements, which are incompatible with the international practice. Turkey, in its turn, took a pronounced anti-Armenian position, unilaterally closing the border with Armenia, continuing to keep Armenia in a blockade. Therefore, it is no coincidence that Turkey's approaches to normalizing relations with Armenia were largely conditioned by the achievements of the Armenian armed forces in Artsakh, because the more obvious these successes, the tougher Turkey's position towards Armenia became. This manifested itself during the liberation of Karvachar (early April 1993) by the armed forces of Armenia, after which Turkey not only closed the border, but also began to accumulate troops near the border with Armenia, but Russia's sharp reaction deterred Turkey from further actions. We consider it appropriate to mention that during the period under discussion, such an approach of Turkey to the issue of normalizing relations with Armenia posed a serious threat to our national security. Analyzing the influence of the economic factor of mutual interest in the Armenian-Turkish relations, it was emphasized that no matter how favorable the development of economic relations with Armenia is for Turkey, Armenia is not of serious interest for Turkey in terms of its economic development. Some activation does not give us grounds to characterize this as a serious breakthrough in the normalization of the Armenian-Turkish relations. Therefore, it is no coincidence that, given a certain perspective of the Armenian-Turkish economic cooperation, the Turkish side tried to create the illusion of some progress in the Armenian-Turkish relations with the Armenian leadership, thereby prompting the Armenian leadership to convince the diaspora to stop encouraging the process of the international recognition of the Armenian Genocide. This circumstance, of course, also testifies to the impact of the process of the international recognition of the Armenian Genocide on the Armenian-Turkish relations. As for the economic factor, the fact that the Armenian leadership did not properly analyze in previous period the initiatives of the Turkish side to intensify economic contacts between the two countries, did not even catch the moment that the economic factor and the Turkish version of the solution to the Karabakh conflict were combined. Meanwhile, with the preconditions put forward, Turkey tried to make Armenia its servant, and through it to dictate its will to the Armenians of the Diaspora. Concerning the Armenian-Turkish contacts at the level of non-governmental organizations, it was noted that the activities of such organizations were initially doomed to failure due to the extremely opposite views of the parties. The leadership of the Republic of Armenia at that time, being aware of such contacts, however, did not properly analyze their possible positive and negative consequences both for the Republic of Armenia and for the Diaspora: it did not express a clear position on this issue.Meanwhile, the subsequent course of the events showed that Turkey, using the presence of such contacts, tried to move the issue of the Armenian Genocide from the political sphere to the sphere of scientific and public discussions, once again striving to stop the process of the international recognition of the Armenian Genocide.By and large, the same goal was pursued by the slogan "zero problems with neighbors" put forward by the Turkish leadership, which, despite the specific steps taken, does not lead to the normalization of the Armenian-Turkish relations. Thus, sometimes positive glimpses in the policy of the Turkish leadership in the relations with Armenia can be explained by various geopolitical interests of Turkey, in particular, the issue of joining the European Union.Specific facts have proved that even the fact of signing the famous Zurich Protocols on October 10, 2009 could not force Turkey to fulfill its obligations, to refuse to put forward preconditions for the establishing diplomatic relations with Armenia.Analyzing the content of the Zurich Protocols, it was noted that this does not fully meet the vital interests of all Armenians, since certain provisions of the protocols, especially the provision on mutual recognition of borders, make it senseless to continue the process of the international recognition of the Armenian Genocide, as well as steps to be taken to overcome consequences.Particular attention was paid to the fact that during the period under discussion a new phenomenon was observed in the process of the international recognition of the Armenian Genocide: some European countries are adopting laws criminalizing the denial of the genocide, some of which cannot be called finalized, which also affects the process itself in future. Summing up the results of the efforts of the second president of Armenia to normalize the Armenian-Turkish relations, it was emphasized that they, like during his predecessors, did not lead to the establishment of diplomatic relations between the two countries, and Turkey, in fact, got one more chance to show the world its "passionate desire" to settle relations with Armenia.Presenting the Centennial of the Armenian Genocide and the further process of recognition in the context of the Armenian-Turkish relations, the article draws special attention to the fact that on the eve of the Centennial of the Armenian Genocide, official Turkey does not change its policy of denial of the Armenian Genocide, nevertheless, it makes some changes into the strategy. The meaning of such changes was the theses put forward by Erdogan and Davutoglu about "common grief" and "fair memory". It was emphasized that such a new manifestation of Turkish denial was no less dangerous, since it was an attempt to equate "executioner" with "victim". It was further noted that this approach of Turkey did not give tangible results, since in the context of the Centennial of the Armenian Genocide, the process of the official recognition and condemnation of the Armenian Genocide by various countries and authoritative international organizations continued. The fact that after the adoption of the resolution on the Centennial of the Armenian Genocide in the Armenian realities the issue of transferring the Genocide to the legal field, in addition to the recognition of the Genocide, and the improvement of the international law, introducing a new wording - “patricide”, was not ignored. In this regard, it was emphasized that the implementation of such an idea, although welcomed, would require tremendous efforts and energy. In addition, the idea was noted that the possibility of implementing these provisions will be much greater if Armenia becomes one of the influential "players" in the region, dictating its own rules of the game. As for the further efforts of the Armenian authorities to establish diplomatic relations between the two countries, it is obvious that it was not endlessly possible to endure Turkey's destructive approach to this issue. Consequently, the speech of the President of the Republic of Armenia on September 20, 2017 at the UN General Assembly was the first logical step towards the abolition of the Zurich Protocols by the Republic of Armenia, a process that came to its logical conclusion on March 1, 2018 by the decree of the President of the Republic of Armenia “On the termination of the procedure for establishing the Armenian Turkish relations”.Not only did Turkey not establish diplomatic relations with Armenia, but 100 years after the Turkish-Armenian war, on September 27, 2020, it made an attempt to forcefully resolve its precondition on the Artsakh question. Through the direct instigation and support to “fraternal” Azerbaijan, it unleashed the war against the Republic of Artsakh and the Republic of Armenia, and, through military aggression, about 75% of the territory of the Republic of Artsakh was captured, not only 7 previously liberated regions, but also Hadrut and Shushi. Not satisfied with all this, on the advice of the same Turkey, Azerbaijan, in May 2021, invaded the sovereign territory of the independent Republic of Armenia, creating a real threat to the existence of the Armenian statehood, a real "threat to the security of the Armenian people", trying to connect Azerbaijan and Turkey through the so-called Zangezur corridor through Nakhichevan for the implementation of the long-standing program of Pan-Turkism.